2019
DOI: 10.1089/neu.2018.6266
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Administration after Traumatic Brain Injury Reduces Mitochondrial Dysfunction and Neurodegeneration

Abstract: Traumatic brain injury (TBI) increases Ca 2+ influx into neurons and desynchronizes mitochondrial function leading to energy depletion and apoptosis. This process may be influenced by brain testosterone (TS) levels, which are known to decrease after TBI. We hypothesized that a TS-based therapy could preserve mitochondrial neuroenergetics after TBI, thereby reducing neurodegeneration. C57BL/6J mice were submitted to sham treatment or severe parasagittal controlled cortical impact (CCI) and were subcutaneously i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 60 publications
(103 reference statements)
1
37
0
Order By: Relevance
“…TBI has been shown to cause significant changes in various mitochondrial functions, including the transport of electrons through the ETC [26,27], the permeability of the mitochondrial membranes [28], and the mitochondrial quality control system [19,29,30]. These phenomena, besides triggering oxidative/nitrosative stress [20,31] and the intrinsic pathway of apoptosis [32], generate a profound derangement of energy metabolism, leading to inadequate ATP supply for the brain’s energy demands [12,15,16,17,25,33]. Given that the brain mostly utilizes glucose as the fuel for its oxidative metabolism [4,5,34], it is highly relevant to elucidate which steps of glucose oxidation TBI principally affects.…”
Section: Discussionmentioning
confidence: 99%
“…TBI has been shown to cause significant changes in various mitochondrial functions, including the transport of electrons through the ETC [26,27], the permeability of the mitochondrial membranes [28], and the mitochondrial quality control system [19,29,30]. These phenomena, besides triggering oxidative/nitrosative stress [20,31] and the intrinsic pathway of apoptosis [32], generate a profound derangement of energy metabolism, leading to inadequate ATP supply for the brain’s energy demands [12,15,16,17,25,33]. Given that the brain mostly utilizes glucose as the fuel for its oxidative metabolism [4,5,34], it is highly relevant to elucidate which steps of glucose oxidation TBI principally affects.…”
Section: Discussionmentioning
confidence: 99%
“…The rat skull cap was carefully removed, the brain was exposed, rapidly removed, the cerebral hemispheres dissected and placed on aluminium tongues pre-cooled in liquid nitrogen, freeze-clamped, and then immersed in liquid nitrogen. The freeze-clamping procedure was introduced to accelerate freezing of the tissue, thus minimizing potential metabolite loss [9,12,15,16]. Tissue homogenization for metabolite analyses was effected as described below.…”
Section: Cerebral Tissue Processing For Biochemical Analysesmentioning
confidence: 99%
“…The severity of this cellular and molecular damage depends on the impact force acting on the cerebral tissue [12]. Mitochondrial dysfunction occurs in the post-injured brain [13,14], causing an imbalance of ATP production and consumption, with consequent energy crisis [15]. This triggers the intrinsic apoptotic pathway [16], and increasing levels of reactive oxygen species (ROS) and reactive nitrogen species (RNS) with associated decreased levels of cell antioxidants [17] causing an insurgence of oxidative/nitrosative stress [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the expression of Bax is significantly upregulated, and the expression of Bcl-2 is downregulated in the TBI model. 48 The NLRP3 inflammasome is a multiprotein oligomer activated by NF-κB and promotes the secretion of IL-1β and IL-18. These cytokines induce pro-inflammatory cell death by activating Bax.…”
Section: Discussionmentioning
confidence: 99%